The IARC perspective on cervical cancer screening - Bouvard, Véronique (2021)
In May 2018, the World Health Organization (WHO) called for a global initiative to eliminate cervical cancer as a public health problem. To achieve this goal, global scale-up of effective vaccination against the human papillomavirus (HPV) as well as screening for and treatment of cervical cancer are required. Cervical cancer screening was evaluated in 2005 by the International Agency for Research on Cancer (IARC) Handbooks program,1 and a reevaluation was deemed to be timely given the major advances in the field since then. The new handbook provides updated evaluations of the effectiveness of screening methods, which were used as a basis for the update of the WHO Guideline for Screening and Treatment of Cervical Pre-cancer Lesions for Cervical Cancer Prevention.2 We convened an IARC Working Group of 27 scientists from 20 countries to assess the evidence on the current approaches to and technologies used in cervical cancer screening with the use of the newly updated Handbooks Preamble3 (Fig. 1) and Table 1).